Study of student satisfaction for "sandwiches" delivery approach / Eric Chan - Chan, Eric (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
The summer trimester system provides students with greater flexibility to plan their study around work or lifestyle commitments, create options for students to commence a degree sooner or at a more convenient time of the year and enable students to fast track their study. There is increasing number of students enrolled in summer trimester. However, it was found that student engagement during summer is less than when those same subjects are delivered during other trimesters. This research investigates using the "Sandwiches" delivery approach to improve the learning relationship with students. This innovative approach includes the first three weeks intensive on-campus delivery with a range of lectures and tutorials. This is followed by six weeks of on-line discussions, quizzes and self-assessment activities to strengthen the students' knowledge and reinforce learning. The last week of summer trimester is revision to confirm theory prior to an examination. Positive responses from student reflected that this approach can be used for other subjects not only in summer trimester but also applicable in other trimesters. In fact, in order to improve course delivery, higher education providers always collect feedback and comment from students and previous research studies have used various methodologies. This paper demonstrates how to use survey plus case study to analyses student satisfaction